Onlay free preputial graft for mid and distal penile hypospadias - Gangopadhyay A; Sharma Shilpa; Mongha Ritesh (Wolters Kluwer Medknow Publications, 2005)
Tubularized free preputial graft for hypospadias repair had been tried in the past and discarded due to high incidence of graft shrinkage causing stricture formation. We have tried to revive the technique using onlay method thus avoiding stricture formation. The technique was used in 33 subjects (Group A) and compared with 33 subjects in control group (Group B) in whom other techniques of urethroplasty were used. The study was a randomized controlled trial. The mean length of the free preputial graft was 22.06 + 4.68 mm (16-35 mm) and breadth was 9.0 + 1.32 mm (7-11 mm). Fistulae developed in 3 patients in group A out of which one healed spontaneously. In group B, 6 patients had fistula formation. Complications developed in 18% cases in group A and 50% cases in group B. There was significant difference between the cosmetic results (p < 0.05) with 58% excellent results in group A and 27% in group B. Free preputial graft onlay urethroplasty has better functional and cosmetic results.